2007
DOI: 10.1080/14634980701351395
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater fishes of the Altiplano

Abstract: Fisheries of the Altiplano, dating from 1500 to 2000 BC, are active in the Andean inter-montane plateau that extends from Ancash, Perú, to Antofagasta, Chile, at altitudes above 3600 m. The ancient and remote nature of these systems has merited the inclusion of many areas as National Parks and RAMSAR sites. Among 58 native fish species, 45 belong to the killifish complex Orestias and the rest to the catfish complex Trichomycterus. The main fishery resources consist of “ispi”, Orestias ispi, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 4 publications
0
46
0
3
Order By: Relevance
“…The nucleotide sequence of O. cuvieri was identical to that of the closely related species O. pentlandii (MNHN A-9594), and just slightly different (two base pairs) from haplotypes found in type specimens of O. ispi, highlighting the very close genetic proximity between morphologically and ecologically well differentiated species within the cuvieri complex. One of the probable causes of the extinction of O. cuvieri is competitive exclusion or predation through the introduction of non-native species such as trouts, salmonids and silversides between 1940 and 1950 (Lauzanne 1992;Parenti 1984a;Vila et al 2007). However, given the genetic similarity among representatives of the cuvieri complex (especially between O. cuvieri and O. pentlandii), we may consider that the mitochondrial genome of the species is still represented in the wild, whether 'extinction' of the morphotype 'O.…”
Section: The Cases Of O Jussiei and O Cuvierimentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleotide sequence of O. cuvieri was identical to that of the closely related species O. pentlandii (MNHN A-9594), and just slightly different (two base pairs) from haplotypes found in type specimens of O. ispi, highlighting the very close genetic proximity between morphologically and ecologically well differentiated species within the cuvieri complex. One of the probable causes of the extinction of O. cuvieri is competitive exclusion or predation through the introduction of non-native species such as trouts, salmonids and silversides between 1940 and 1950 (Lauzanne 1992;Parenti 1984a;Vila et al 2007). However, given the genetic similarity among representatives of the cuvieri complex (especially between O. cuvieri and O. pentlandii), we may consider that the mitochondrial genome of the species is still represented in the wild, whether 'extinction' of the morphotype 'O.…”
Section: The Cases Of O Jussiei and O Cuvierimentioning
confidence: 99%
“…Its main area of distribution covers the Lake Titicaca and most of the Andean Altiplano, from southern Peru to Bolivia and northeastern Chile. It represents one of the three native teleostean genera endemic to the area (Parenti 1984a;Vila et al 2007;Villwock 1986). Orestias pupfishes are externally characterized by the absence of pelvic fins, a reduced and irregular body squamation pattern and a unique head pore pattern (Parenti 1984a;Villwock 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Adicionalmente a esta carencia, se suma la falta de información relacionada con las características abióticas de muchos de los sistemas donde la ictiofauna habita. Este es el caso de los sistemas acuáticos del Altiplano sur-oeste (17°-22°S), donde las actividades antrópicas a las cuales se han visto sujetos los recursos acuáticos, han acelerado procesos naturales como la eutrofi zación y la salinización (Vila et al 2007a). Los estudios ictiológicos llevados a cabo en estos sistemas altiplánicos, en su mayoría se han enfocado en aspectos sistemáticos de estos (Parenti 1984;Vila & Pinto 1986;Vila 2006;Vila et al 2007b), otros relacionados con su reproducción en cautiverio (Jara et al 1995) y fi logeografía (Lüssen et al 2003).…”
Section: Introductionunclassified
“…According to the values estimated for the Fulton's condition factor (Nash et al 2006), all individuals captured showed appropriate development conditions with an optimal allometric length/weight relationship for individuals developing in the wild (Murphy and Willis 1996), which indicates an adequate supply of resources. CPC-2010-128, CPC-2010-129, CPC-2010-130, CPC-2010-131 CPC-2010-028, CPC-2011-071 CPC-2011 The presence of Salvelinus fontinalis in the southern part of the Peruvian Andes is undeniable, and the speciesas suggested by Vila et al (2007) -is possibly distributed throughout the region adjacent to the endorheic basin of Lake Titicaca. According to historical information, Salvelinus fontinalis (among other Salmonid species) was introduced to the region, and its current presence corresponds to isolated populations with few individuals due to its low quality as a focal species for Aquaculture Programs (compared to the Rainbow Trout) and the high fishing pressure experienced by Salmonids in the lotic environments of the high Andes.…”
mentioning
confidence: 99%
“…in Lake Titicaca was poor and unsuccessful and although the Salmo trutta could be registered in the Ilave River up to 1970, for 1988 only the presence of the Rainbow Trout was reported for the lake and its endorheic basin. In an article on freshwater fish of the Altiplano, a plateau between the Eastern and Western Andean mountain ranges, where Lake Titacaca is located, Vila et al (2007) report that the Salmonid species introduced to the region included Salmo trutta, Salvelinus fontinalis and Salvelinus namaycush, however according to the authors none of these three species has been recorded recently.…”
mentioning
confidence: 99%